2011
DOI: 10.1227/neu.0b013e318233868f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Diagnostic Utility of Electromyography, Ultrasonography, Computed Tomography, and Magnetic Resonance Imaging in Idiopathic Carpal Tunnel Syndrome Determined by Clinical Findings

Abstract: EMG or US could be used as the first-step test in most cases. If they are both available, EMG should be the first choice. They may be performed together when diagnosis is challenging. CT may especially be preferred for bone-related pathological conditions, whereas MRI may be preferred for soft tissue-related pathological conditions. Even though imaging studies have been proven to be powerful diagnostic tools for CTS, no conclusive information currently exists to support replacing EMG with imaging studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 59 publications
1
26
0
1
Order By: Relevance
“…The electrophysiological studies usually show the level of the lesion, but do not provide anatomical information about the nerve or its surroundings. In the last few years, ultrasonography (US) has been shown to be useful diagnostic tools in CTS, providing information on the median nerve and surrounding structures4,6,13,23). A few papers have been published in neurosurgery literature regarding diagnostic utility of ultrasonography in carpal tunnel syndrome1,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophysiological studies usually show the level of the lesion, but do not provide anatomical information about the nerve or its surroundings. In the last few years, ultrasonography (US) has been shown to be useful diagnostic tools in CTS, providing information on the median nerve and surrounding structures4,6,13,23). A few papers have been published in neurosurgery literature regarding diagnostic utility of ultrasonography in carpal tunnel syndrome1,6).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, ultrasonography (US) has been shown to be useful diagnostic tools in CTS, providing information on the median nerve and surrounding structures4,6,13,23). A few papers have been published in neurosurgery literature regarding diagnostic utility of ultrasonography in carpal tunnel syndrome1,6). To our knowledge, publication has not been available, describing measurements of ultrasonographic parameters for the diagnosis of CTS, compared with electrodiagnostic findings as well as clinical severity, assessed by historical-objective scale9).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study comparing the diagnostic accuracy of EDS, US, CT and MRI in CTS, compared to clinical diagnosis as a reference standard, showed that these four tests had similar accuracy for the diagnosis of CTS. 16 The existing evidence does not support using either EDS or imaging tests over history and physical exam for CTS diagnosis. Furthermore, EDS prior to CTR was associated with prolonged time to surgery, additional out of pocket costs, and greater total costs in a national study.…”
Section: Discussionmentioning
confidence: 99%
“…Die bildgebenden Verfahren -hochauflösende Neurosonografie, Computertomografie und Kernspintomografie -gewinnen zunehmende Bedeutung bei der Diagnostik des KTS (s. ▶ , sind allerdings noch nicht erste Wahl (Deniz et al 2012). Allenfalls die Sonografie ist ein Konkurrenzverfahren zur Elektrophysiologie und könnte dieser den ersten Platz streitig machen (Fowler et al 2011 (Wu et al 2004).…”
Section: Bildgebende Verfahrenunclassified